Flickering of a diffusion flame: An innovative way of stabilization by a mechanical actuator. (December 2022) - Sayed-Kassem, Ahmad; Gillon, Pascale; Idir, Mahmoud; Gilard, Virginie
Abstract: Flickering is an oscillating instability of a diffusion flame. An experimental study has been performed on two different diffusion flame of methane and ethylene to elucidate flickering instability and controlling it by the mean of a mechanical stabilizer. Flame imaging and temporal evolution of transmitted signal methods have been employed to monitor the flame behavior and measure flickering frequency. Three different regimes of stability are identified: stable, transient, and full unstable. The measured flickering frequency of ethylene flame is 11 Hz and it is demonstrated to be independent of fuel jet velocity. The calculated vortex mean velocity is 500 mm/s and 800 mm/s without and with "pinch-off" formation respectively and the "pinch-off" velocity is around 1450 mm/s. Moreover, the ability of a mechanical actuator to stabilize the flame has been demonstrated for methane and ethylene. The experiment reveals the existence of a limit of stabilizing height at each flowrate. However, positioning stabilizer below the burner shows a limited effect. Numerical simulation shows a smoother effect of stabilizer on air streamlines around the flame limiting the action of vortex on the flame. These results prove that flickering instability could be suppressed by only controlling the air surrounded the flame. Highlights: Flickering instability of diffusion flame has been studied by flame imaging and temporal recording of transmitted signal. Three different regimes of instability are identified depending on fuel flowrate. A flickering frequency of 11 Hz is measured for ethylene diffusion flame with a "pinch-off" velocity of 1450 mm/s. The controllability of flickering by a mechanical stabilizer is proved for methane and ethylene diffusion flames.